Special issue: tissue engineered biomaterials and drug delivery systems - Ribeiro, Viviana Pinto (2022)
[Excerpt] Current advances in biomaterials processing and engineering for drug delivery have allowed interesting progressed in biomedical field. Such developments were only possible by the intervention of tissue engineers, physical and chemical scientists, biologists, and clinicians, that together developed innovative strategies and technologies capable of addressing a higher number and patient-specific requirements [1].